Scientia Sacra Seyyed Hossein Nasr Sebagai Landasan Filosofis Pengembangan Ekowisata Teosentris - Moh. Anang Khumaidi; Cahaya Zakia A’yunin Juwita Hanum; Achmad Khudori Soleh (Yayasan Azhar Amanaa Yogyakarta, 2026)
The contemporary ecotourism industry faces a moral crisis characterized by widespread greenwashing practices and the commodification of cultural spaces. This problem stems from an epistemological crisis driven by the dominance of modern, Cartesian-mechanistic, and anthropocentric science. This study aims to: (1) deconstruct the epistemological crisis underlying contemporary ecotourism through Seyyed Hossein Nasr’s Scientia Sacra perspective; (2) conceptualize the philosophical foundations of teocentric ecotourism rooted in the reorientation of the Pontifical Man; and (3) formulate the operational pillars of the Theocentric Ecotourism model as an alternative paradigm. Using a library research method with philosophical and historical-intellectual approaches, data were analyzed through hermeneutics, comparative-contrastive analysis, and conceptual synthesis. The findings reveal that the failure of ecotourism originates from Promethean Man reducing nature to a passive material object for commercial profit. In response, Scientia Sacra restores human position as Pontifical Man (bridge/steward) who views nature as a theophany (tajallī) or ayat kawniyyah. This study proposes three operational pillars for Theocentric Ecotourism: (1) Spiritual-Educational (Sacred Interpretation); (2) Ecological-Cosmic (Cosmic Stewardship); and (3) Socio-Cultural (Community Resacralization). By integrating transcendental dimensions and adopting a niche market strategy based on premium spiritual value, this model moves beyond conventional sustainable tourism and Halal Tourism to achieve holistic cosmic conservation and economic justice